Elevating 'TutorYuk' Online Peer Tutoring Services Through Information System: A Design Thinking Framework Approach - Jesslyn Alvina Seah; Gilberto Dennis G E Sidabutar; Rafael Christian; Siemens Benyamin Tjhang; Yoel Kristian; Yerik Afrianto Singgalen (Universitas Bina Darma, 2023)
Through applications supporting informal education services, the development of information technology during the fourth industrial revolution has promoted the growth of the education industry in Indonesia. This study uses the Design Thinking framework to design and analyze information systems for the online peer tutoring services known as TutorYuk. The stages in system design are as follows: empathize stage, namely the process of identifying user needs and classifying practical problems related to requirements in the informal education sector; define the location, analyze the priority of user needs and issues that need to be solved through information systems; the idea stage, the process of networking aspirations related to solutions to problems in the education sector that shows the urgency of system design; prototype stage, design system flow and function and visualization of application interfaces; Testing stage, testing system performance. The findings of this study demonstrate that TutorYuk is built to suit student needs for learning help based on course names and instructor qualities chosen by users. The duration and experience of the instructor are considered when providing tutoring services so that they can be tailored to the client's needs. Consequently, by offering digital media to service suppliers (tutors) and service recipients, TutorYuk can become a commercially successful application (tutees).